Synthesis and study of antimicrobial activity of new tetralone esters - Hucchegowda, Krishna Mudeenahally; Basavaiah, Basavaraju Yeriyur; Basavaiah, Umesha; Basavaiah, Shivakumar Santhekasalagere (European Journal of Chemistry, 2014)
Podophyllotoxin belongs to the class of cyclolignan family of natural products, which exhibits strong antimitotic, anti-AIDS (HIV), antitropical skin disease, antimalarial, virucidal, fungicidal and other biological activities. The new tetralone esters (9a-d) of podophyllotoxin analogues were synthesized in good yields by chalcone route to study their structure-activity relationship. All the products obtained were characterized by spectral and elemental analysis data and they were screened for antimicrobial activity. Compounds 9b and 9c were shown significant antibacterial and antifungal activities.